MANAGEMENT’S ATTITUDE TOWARDS EMPLOYEES WORKING IN THE RETAIL SHOP IN BANGLADESH - Uddin, Md. Mayeen (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
According to Well-Known National Dailies, Retail Shop contributes the most to the country’s economy, with the highest gross value addition (GVA) worth Tk 208,700 crore, or nearly 63%. The retail sector of Bangladesh has already employed over six million (60 lahks) people. Sometimes we notice that employees working in retail shops complain against their Owner/Management regarding their benefits and opportunities that specify Management’s Attitude towards them. Very few research studies were conducted regarding employees working in retail shops in Bangladesh. This study aimed to identify management’s attitude towards employees working in retail shops in Bangladesh by exploring some factors that specify attitude. The study used descriptive statistics design. This study was based on a field survey conducted in Chattogram, Bangladesh. The cluster Random sampling technique was used to pick up the sample. The questionnaire was presented to 160 respondents in person, and all of them responded; hence analyzed and presented in frequency distribution tables with their corresponding percentages and some statistical analysis. Other data were sourced from published academic journals, articles, and other relevant materials on the internet. The results indicate that Management in Retail shops has a mildly negative attitude towards their employees. The Study suggests that management should focus more on employees’ financial and Non-financial benefits as those indicate their attitude towards employees in retail shops in Bangladesh. JEL Classification Codes: J53, M12, M54.